Process improvement to increase rates of sperm-banking in AYA patients newly diagnosed with cancer: an institutional experience - Sandheinrich, Taryn; Schultz, Katie; Hayashi, Robert J.; Hoefgen, Holly (Frontiers in Adolescent Medicine, 2024)
Background Despite ASCO and COG recommendations, increasing the rate of sperm-banking for newly diagnosed AYA males with cancer remains difficult. Multiple barriers to fertility preservation at pediatric institutions have been well described. Numerous logistical barriers can impede successful sperm cryopreservation. We analyzed our institution's experience in optimizing workflows to improve sperm-banking rates. Our processes improvement included: (1) striving for a fertility consult for each newly diagnosed male, (2) utilization of a member of the oncology provider team serving as a fertility navigator (FN) providing fertility consultation and counseling services. Methods Sperm banking rates at St. Louis Children's Hospital were reviewed and compared for three discrete calendar years spanning the implementation of these enhancements (2017, 2019, 2022). We plotted process changes over time to assess their impact on the rate of successful sperm-banking in eligible AYA males newly diagnosed with cancer. Results The rate of consults for sperm banking prior to therapy increased from 18% in 2017 to 91% in 2022 (p = .0003). Rates of sperm banking in eligible males increased from 18% to 82% (p = .0015) between 2017 and 2022. Conclusion Embedding a FN who is also a member of the primary oncology team increases not only the fertility consult rate but also the rate of successful sperm-banking in AYA males who are newly diagnosed with cancer at pediatric institutions.